2018
DOI: 10.3389/fpls.2018.00653
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mapping of the Clubroot Resistance Gene CRd in Chinese Cabbage (Brassica rapa ssp. pekinensis)

Abstract: The rapid spread of clubroot disease, which is caused by Plasmodiophora brassicae, threatens Brassicaceae crop production worldwide. Breeding plants that have broad-spectrum disease resistance is one of the best ways to prevent clubroot. In the present study, eight Chinese cabbage germplasms were screened using published clubroot-resistant (CR) loci-/gene-linked markers. A CR gene Crr3 potential carrier “85-74” was detected which linked to marker BRSTS61; however, “85-74” shows different responses to local pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 52 publications
0
94
0
Order By: Relevance
“…Clubroot disease jeopardizes crop cultivation and yield by causing the development of large galls on the roots that reduce the plant's ability to absorb water and nutrients from the soil. Although clubroot resistance (CR) genes have been identified, mainly in Brassica rapa [16][17][18][19][20][21][22][23], the detailed mechanism of CR remains unclear. However, the suppression of clubroot by exogenous SA was also reported in broccoli (Brassica oleracea) [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clubroot disease jeopardizes crop cultivation and yield by causing the development of large galls on the roots that reduce the plant's ability to absorb water and nutrients from the soil. Although clubroot resistance (CR) genes have been identified, mainly in Brassica rapa [16][17][18][19][20][21][22][23], the detailed mechanism of CR remains unclear. However, the suppression of clubroot by exogenous SA was also reported in broccoli (Brassica oleracea) [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that Botrytis cinerea regulates both pathways to enable infection of tomato [26]. A novel CR gene (CRd) conferring complete resistance to a specific pathotype of P. brassicae was recently identified in B. rapa [23]. However, the mechanism of action of the CRd gene product and its association with phytohormone signaling at different developmental stages of P. brassicae has yet to be elucidated, and we suspect that the hormonal signal transduction pathway involved in clubroot disease resistance may be distinct due to the different CR genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al 149 adopted KASP markers and BSR-seq strategies to finely map Rcr2 to a 0.4 cM interval, identifying two TIR-NBS-LRRs as candidates. Using BSA-seq, Pang et al 150 identified the new locus CRd in a 60 kb region on chromosome A03, which is located upstream of Crr3.…”
Section: Clubrootmentioning
confidence: 99%
“…The secondary resting zoospores in turn infect cortical cells and form secondary plasmodia, which are the key cause of swollen roots (Rolfe et al 2016). The clubroot hinders the absorption and transport of water and nutrients in plants (Pang et al 2018), causing crop yield reduction.…”
mentioning
confidence: 99%